A REVERBERATING ECHO FROM THE FAR PAST THE ROLE OF THE ASMARAKANDHI IN JAVA’S ISLAMIZATION PROCESS - Edwin P Wieringa (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2022)
The Asmarakandhi, which is a Javanese translation of an Arabic book entitled Bayān ‘Aqīdat al-Uṣūl by Abū’l Laith Naṣr b. Muḥammad al-Samarqandī (d. 373/983), is to be discussed in this study. Abū’l Laith’s text belongs to the earliest theological primers in Java, possibly first introduced on Java’s North Coast by Chinese merchants from the Ḥanafī legal school. For many centuries, Asmarakandhi was an authoritative source for new students of Islam before it fell into general disuse during the course of the twentieth century. Contrary to common belief, Abū’l Laith’s text is not as simple as it seems, containing several controversial issues.